Templars in Bologna: a multidisciplinary approach - Bagni, Giampiero (Military religious orders, 2024)
Introduction -- Bologna in the age of the Templars (1115-1315) -- The Crusades and Templar establishments along the Via Emilia under the Archbishops of Ravenna -- Data analysis of archaeological and architectural Surveys from Bologna's Templar House -- Templar properties and wine production in Bologna and its hinterland -- Peter of Bologna: the life and identity of a Templar Brother -- Military orders in Bologna -- Conclusions -- Appendix A Scientific data (results) -- Appendix B Inventory of Bolognese Templar properties (March 1309) -- Appendix C Various important primary sources -- Appendix D Prosoprographical research list regarding Bologna Templar Brothers